Experimental study and Taguchi analysis on LED cooling by thermoelectric cooler integrated with microchannel heat sink. (15th May 2019) - Lin, Xiaohui; Mo, Songping; Jia, Lisi; Yang, Zhi; Chen, Ying; Cheng, Zhengdong
Highlights: LED cooling by thermoelectric cooler integrated microchannel heat sink is proposed. The relative importance of the factors was revealed by the Taguchi method. The proposed LED + TEC + WMHS device showed excellent cooling performance. The LED headlight can be cooled to temperature lower than the coolant temperature. Cooling system and factor levels for different applications were recommended. Abstract: Effective thermal management is crucial for light-emitting diodes (LED). Thermoelectric cooler (TEC) and microchannel heat sink (MHS) have been demonstrated to be effective for thermal management of LED. However, neither the combination of these two methods, nor the dominant factors which could be effectively adjusted to control the LED temperature, have been reported. In this study, a cooling device integrating TEC and water-cooled microchannel heat sink (WMHS) is proposed to improve the thermal management of high-power LED headlights. The start-up performance of the proposed device, LED + TEC + WMHS, was evaluated and compared with three different systems, namely LED + WMHS, LED + AHS (air-cooled heat sink), and LED + TEC + AHS. Experimental results have demonstrated the best performance of the LED + TEC + WMHS device. Orthogonal experiments based on the Taguchi method were conducted to reveal dominant factors among four variables, including TEC current, water inlet temperature, water flow velocity, and ambient temperature. The results show that effects of all the factors were significant while the TEC current has most important influence on the performance. The variation of the thermal management performance with the levels of the factors were investigated. The LED temperature was only 60.0 °C even at severe working conditions ( T a  = 80 °C, T i  = 55 °C) and moderate cooling input ( I TEC  = 2 A, u  = 0.49 m/s), indicating great thermal management performance of the proposed method. Choosing a cooling system and adjusting the factor levels for different applications were recommended.